Laryngeal Reconstruction Using Tissue‐Engineered Implants in Pigs: A Pilot Study. (28th November 2020) - Brookes, Sarah; Zhang, Lujuan; Puls, Theodore J.; Kincaid, John; Voytik‐Harbin, Sherry; Halum, Stacey
Abstract : Objective/Hypothesis: There are currently no treatments available that restore dynamic laryngeal function after hemilaryngectomy. We have shown that dynamic function can be restored post hemilaryngectomy in a rat model. Here, we report in a first of its kind, proof of concept study that this previously published technique is scalable to a porcine model. Study Design: Animal study. Methods: Muscle and fat biopsies were taken from three Yucatan minipigs. Muscle progenitor cells (MPCs) and adipose stem cells (ASCs) were isolated and cultured for 3 weeks. The minipigs underwent a left laterovertical partial laryngectomy sparing the left arytenoid cartilage and transecting the recurrent laryngeal nerve. Each layer was replaced with a tissue‐engineered implant: 1) an acellular mucosal layer composed of densified Type I oligomeric collagen, 2) a skeletal muscle layer composed of autologous MPCs and aligned oligomeric collagen differentiated and induced to express motor endplates (MEE), and 3) a cartilage layer composed of autologous ASCs and densified oligomeric collagen differentiated to cartilage. Healing was monitored at 2 and 4 weeks post‐op, and at the 8 week study endpoint. Results: Animals demonstrated appropriate weight gain, no aspiration events, and audible phonation. Video laryngoscopy showed progressive healing with vascularization and re‐epithelialization present at 4 weeks. On histology, there was no immune reaction to the implants and there was complete integration into host tissue with nerve and vascular ingrowth. Conclusions: This pilot study represents a first in which a transmural vertical partial laryngectomy was performed and successfully repaired with a customized, autologous stem cell‐derived multi‐layered tissue‐engineered implant. Level of Evidence: NA Laryngoscope, 131:2277–2284, 2021